2017
DOI: 10.1016/j.ajme.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey of parental care-seeking behavior for febrile illness among under-five children in Nigeria

Abstract: Background: Infections are a common cause of childhood morbidity and mortality in developing countries. Proper management of these conditions in appropriate health facilities provides the best opportunity for survival and reducing disability. Aims: To evaluate the care-seeking behavior by parents of under-five children with fever in Nigeria and determine household characteristics associated with appropriate care-seeking. Material and methods: The study is a secondary analysis of 2013 Demographic and Health Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 12 publications
9
29
1
Order By: Relevance
“…On the other hand, our finding is lower than previous studies conducted in the rural parts of Niger (70.4%) and Uganda (76%) [17, 19]. The finding of the study also showed that health care utilization for fever illness was higher than a study conducted in Nigeria [32]. On the contrary, lower than a study conducted in a rural area of Tanzania [18].…”
Section: Discussioncontrasting
confidence: 86%
“…On the other hand, our finding is lower than previous studies conducted in the rural parts of Niger (70.4%) and Uganda (76%) [17, 19]. The finding of the study also showed that health care utilization for fever illness was higher than a study conducted in Nigeria [32]. On the contrary, lower than a study conducted in a rural area of Tanzania [18].…”
Section: Discussioncontrasting
confidence: 86%
“…Our study found age of children as a significant predictor of health care use for childhood diarrhea and fever/cough. Other studies in Bangladesh, Ethiopia, Zambia and Nigeria also found that children in the lower age group were more likely to receive treatment [16,19,20,30]. This pattern may be due to the fact that parents usually perceive their children at the early stage as being especially "delicate" [30].…”
Section: Discussionmentioning
confidence: 92%
“…This may be linked to the fact that children from richest households may be enjoying alternative medical care such as home treatment by medical personnel. Employment status of mothers has a significant impact on health care seeking behaviour for their children as working women are more likely to present their children for measles vaccine and more likely to seek medical care when their children have fever or cough [ 25 – 27 ]. It may be that working women have the ability to pay for treatment whenever they present their children for medical care, something which the non-working women may not be able to do on their own.…”
Section: Discussionmentioning
confidence: 99%